Heparin rebound in patients undergoing off-pump coronary artery bypass grafting surgery: a single-center retrospective study - Fei Jiang; Yang Xu; Shan-shan Hu; Jin-quan Wang; Yun-tai Yao; the Evidence in Cardiovascular Anesthesia (EICA) Group (Journal of Cardiothoracic Surgery)
Abstract Background Heparin, an anticoagulant used in cardiac surgery, can result in heparin rebound (HR), where it returns postoperatively despite being neutralized with protamine. This study was designed to investigate the prevalence of HR in patients undergoing off-pump coronary artery bypass grafting (OPCAB) and evaluate the impact of HR on their short-term outcomes. Methods HR was defined by a 10% increase in activated coagulation time (ACT) following two hours of heparin neutralization with protamine, bleeding over 200 mL/h, and abnormal laboratory coagulation examination results. We analyzed 503 OPCAB patients aged 31–80 years from September 2019 to June 2022, who were categorized into HR (n = 56) and Non-HR (n = 447) groups. The primary outcome was postoperative bleeding volume. Secondary outcomes included the incidence of postoperative reoperation for bleeding, allogenic blood transfusion incidences and volumes, and laboratory variables. Results Significant differences were observed in preoperative platelet counts (P < 0.001) and the ACT measured 2 h post-heparin neutralization (P = 0.012). The group HR exhibited higher 24-hour bleeding volumes, increased reoperation rates, and greater total bleeding volumes (all P < 0.001). Conclusions Postoperative HR was found to be prevalent in OPCAB patients and increased bleeding risks. These findings indicate the need for future randomized controlled trials to confirm the impact of HR and guide patient blood management.